2013
DOI: 10.1136/sextrans-2013-051184.0113
|View full text |Cite
|
Sign up to set email alerts
|

O06.1 Evaluation of 5 Different Tests For Trichomonas Vaginalis (TV) Infection and Cost Effective Planning For Clinical Implementation

Abstract: Pipelle, and the tissue was split for microbiological and histological assessment. Cultivated microorganisms were identified using phenotypic and genotypic characteristics. Fisher's exact tests were used to assess the association between microorganisms and endometritis (plasma cells ± neutrophils). Results Of 136 women with clinical PID, 55 (40%) had histologic evidence of endometritis, and endometrial GC and/or CT was associated with endometritis (29% vs. 6%, P < 0.001). In addition to STIs, a broad range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was not clear why the prevalence of TV in this study was low as most studies have shown that a higher prevalence of TV is found in women above the age of 30 years, which was the age for a majority of participants in this study. The low GC and TV prevalence could be explained by the fact that molecular methods were used for the detection of CT while GC was detected by culture while TV was detected by wet mount whose sensitivity varies from 38 to 82 % [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was not clear why the prevalence of TV in this study was low as most studies have shown that a higher prevalence of TV is found in women above the age of 30 years, which was the age for a majority of participants in this study. The low GC and TV prevalence could be explained by the fact that molecular methods were used for the detection of CT while GC was detected by culture while TV was detected by wet mount whose sensitivity varies from 38 to 82 % [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Meanwhile, a preliminary assessment of the cost implications of TV NAATs suggests that while initial outlay costs may be high if the relevant processing system is not already in place, there may be savings in overall labour costs. 16 Without national prevalence data on the burden of asymptomatic infection, determining a prevalence threshold at which to offer universal screening is difficult. However, it is probably not justified to continue in our very low prevalence setting.…”
Section: Discussionmentioning
confidence: 99%